Antioxidant properties and cytotoxic effects of Oxalis corniculata on human Hepatocarcinoma (Hep-G2) cell line: an in vitro and in silico evaluation - Sachin Gudasi; Shankar Gharge; Rahul Koli; Kalpana Patil (SpringerOpen, 2023)
Abstract Background Oxalis corniculata is a well-known medicinal plant used in folk medicine for the management of many diseases. The aim is to determine the physico-chemical properties, microscopic study, phytochemical properties, in-silico, in-vitro antioxidant and anticancer activity on human Hepatocarcinoma (Hep-G2) cell line of O. corniculata plant extract. Results Microscopical study reaveals that presence of pericyclic fibres, starch gains, trichomes etc, and phytochemical screening is carried to find out secondary metabolites. The molecular docking study concluded that some of the phytocompounds showed inhibition of epidermal growth factor receptor tyrosine kinase domain (PDB ID: 1M17) inhibitor. Furthermore, ADMET and drug likeness study hints some of phytocompounds may act as lead for anticancer drug discovery and development. Among selected phytocompounds, compound apigenin possesses − 7.90 kcal/mol as compared to standard drug doxorubicin possesses − 7.63 kcal/mol against the epidermal growth factor receptor tyrosine kinase. The plant extract shown antioxidant activities based on the different tests were performed. The hydroalcoholic plant extracts were found to be selectively cytotoxic in vitro to human Hepatocarcinoma (Hep-G2) cell line with IC50values 34.494 ± 0.42 µg/ml and EAF showed at IC50 value 30.245 ± 0.58 µg/ml of the cells were inhibited at the concentration of 50 µg/ml as compared with standard doxorubicin at IC50 value 24.8939 ± 0.25 µg/ml, respectively. Conclusion The present study concluded that O. corniculata possesses potential antioxidant and cytotoxic properties based upon the computer aided drug design models and in-vitro activity.